Effect of Different Modalities of Purgative Preparation on the Diagnostic Yield of Small Bowel Capsule for the Exploration of Suspected Small Bowel Bleeding: A Multicenter Randomized Controlled Trial. (17th February 2022) - Rahmi, Gabriel; Cholet, Franck; Gaudric, Marianne; Filippi, Jérôme; Duburque, Clotilde; Bramli, Slim; Quentin, Vincent; Alavi, Zarrin; Nowak, Emmanuel; Saurin, Jean Christophe; Cellier, Christophe; Quénéhervé, Lucille; et al.
Abstract : INTRODUCTION: The aim of our study was to compare clear liquid diet with 2 different polyethylene glycol (PEG)-based bowel preparation methods regarding diagnostic yield of small bowel capsule endoscopy (SBCE) in patients with suspected small bowel bleeding (SBB). METHODS: In this prospective multicenter randomized controlled trial, consecutive patients undergoing SBCE for suspected SBB between September 2010 and February 2016 were considered. Patients were randomly assigned to standard regimen, that is, clear fluids only (prep 1), standard regimen plus 500 mL PEG after SBCE ingestion (prep 2), or standard regimen plus 2 L PEG plus 500 mL PEG after SBCE ingestion (prep 3). The primary outcome was the detection of at least one clinically significant lesion in the small bowel. The quality of small bowel cleansing was assessed. A questionnaire on the clinical tolerance was filled by the patients. RESULTS: We analyzed 834 patients. No significant difference was observed for detection of P1 or P2 small bowel lesions between prep1 group (40.5%), prep 2 group (40.2%), and prep 3 group (38.5%). Small bowel cleansing was improved in prep 2 and 3 groups compared with that in prep 1 group. Compliance to the preparation and tolerance was better in prep 2 group than in prep 3 group. DISCUSSION: Small bowel purgative before SBCE allowed better quality of cleansing. However, it did not improve diagnostic yield of SBCE for suspected SBB.